L'arrêt Morgentaler et l'article 7 de la Charte canadienne des droits et libertés - Hartney, Michael (Les Cahiers de droit, 1988)
The author provides a critical analysis of the recent Supreme Court judgment in the Morgentaler case. Focussing on an examination of the main question addressed to the Court, that is the compliance of Criminal Code Section 251 with the Canadian Charter, he examines the various motives that led the judges to declare Section 251 unconstitutional. While underlining various weaknesses in the judges' reasoning, he criticizes Section 7 as being too wide and a source of future confusion.